Emergence of ST63 Pandrug-Resistant Acinetobacter pittii Isolated From an AECOPD Patient in China - Yang, Ling; Dong, Ning; Xu, Chen; Ye, Lianwei; Chen, Sheng (Frontiers in Cellular and Infection Microbiology, 2021)
Acinetobacter sp. is among the ESKAPE organisms which represent the major nosocomial pathogens that exhibited a high resistance rate. A. pittii, frequently associated with antimicrobial resistance particularly to carbapenems, is one of the most common Acinetobacter species causing invasive infection. Pandrug resistant A. pittii has rarely been reported. Here, we report the case of a patient with acute exacerbations of chronic obstructive pulmonary disease three years after double lung transplantation and developed severe pneumonia associated with pandrug resistant A. pittii infection. Phenotypic and genomic characteristics of this pandrug resistant isolate (17-84) was identified, and the mechanisms underlying its resistance phenotypes were analyzed. Isolate 17-84 belonged to ST63, carried a non-typable and non-transferable plasmid encoding multiple acquired resistance genes including carbapenemase gene blaOXA-58. Point mutations and acquired resistance genes were identified which were associated with different drug resistance phenotypes. To our knowledge, this is the first detailed phenotypic and genomic characterization of PDR A. pittii causing severe infections in clinical settings. Findings from us and others indicate that A. pittii could serve as a reservoir for carbapenem determinants. The emergence of such a superbug could pose a serious threat to public health. Further surveillance of PDR A. pittii strains and implementation of stricter control measures are needed to prevent this emerging pathogen from further disseminating in hospital settings and the community.